An imputation platform to enhance integration of rice genetic resources - Wang, Diane R.; Agosto-Pérez, Francisco J.; Chebotarov, Dmytro; Shi, Yuxin; Marchini, Jonathan; Fitzgerald, Melissa; McNally, Kenneth L.; Alexandrov, Nickolai; McCouch, Susan R. (Springer, 2018)
As sequencing and genotyping technologies evolve, crop genetics researchers accumulate increasing numbers of genomic data sets from various genotyping platforms on different germplasm panels. Imputation is an effective approach to increase marker density of existing data sets toward the goal of integrating resources for downstream applications. While a number of imputation software packages are available, the limitations to utilization for the rice community include high computational demand and lack of a reference panel. To address these challenges, we develop the Rice Imputation Server, a publicly available web application leveraging genetic information from a globally diverse rice reference panel assembled here. This resource allows researchers to benefit from increased marker density without needing to perform imputation on their own machines. We demonstrate improvements that imputed data provide to rice genome-wide association (GWA) results of grain amylose content and show that the major functional nucleotide polymorphism is tagged only in the imputed data set.